2003
DOI: 10.7202/007368ar
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Systematic Occupational Health and Safety Management

Abstract: Summary The promotion of systematic occupational health and safety management (SOHSM) represents a comparatively recent but significant realignment of regulatory strategy that has been embraced by many, if not most, industrialized countries. As yet there has been little critical evaluation of the origins and implications of this shift, and to what extent the experience of these measures differs between countries. This article seeks to start the process of answering these questions by comparing SOHSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…British and Australian studies (Walters, ; Walters et al ., ) have found that worker representation and consultation produced better outcomes in OHS than management acting alone. Similar studies have also suggested that trade union presence positively impacts on OHS (Fairbrother, ; Saksvik and Quinlan, ). Additionally, the existence of a broad framework of participative practices through unions, and works councils as exist in European countries, is likely to impact on the effectiveness of specialised OHS committees (Harris, ; Knudsen, ).…”
Section: Employee Participationmentioning
confidence: 57%
“…British and Australian studies (Walters, ; Walters et al ., ) have found that worker representation and consultation produced better outcomes in OHS than management acting alone. Similar studies have also suggested that trade union presence positively impacts on OHS (Fairbrother, ; Saksvik and Quinlan, ). Additionally, the existence of a broad framework of participative practices through unions, and works councils as exist in European countries, is likely to impact on the effectiveness of specialised OHS committees (Harris, ; Knudsen, ).…”
Section: Employee Participationmentioning
confidence: 57%
“…We acknowledge that this study is limited both by its sample size and its reliance on unionized worker representatives. Our findings may also not generalize across other national and industrial contexts, although we suspect they will, given the many similar legislative, technical and corporate conditions in other jurisdictions (Saksvik and Quinlan, 2003;Walters, 1996c). Further research is also needed to confirm the existence of the different forms of representation identified here and the claim that they have different impacts on working conditions.…”
Section: Conclusion: Knowledge Activism As a Successful Adaptationmentioning
confidence: 77%
“…2000; Gallagher et al . 2001; Saksvik and Quinlan 2003; Vinodkumar and Bhasi 2011). According to Frick and Wren (2000, p. 19), systematic OHS management ‘aims to identify sources of injury and ill‐health early in the production process and to produce countermeasures before injury or ill health occurs’.…”
Section: Ohs Literaturementioning
confidence: 99%
“…Over the last twenty years, there has been a growing body of literature on what appears to be a global trend in the adoption of systematic OHS management (see for example , Bluff 2003;Borys 2000;Gallagher et al 2001;Saksvik and Quinlan 2003;Vinodkumar and Bhasi 2011). According to Frick and Wren (2000, p. 19), systematic OHS management 'aims to identify sources of injury and illhealth early in the production process and to produce countermeasures before injury or ill health occurs'.…”
Section: Systematic Ohs Management Studiesmentioning
confidence: 99%